Analysis of some factors driving ecological sustainability in construction firms - Bamgbaded, J. A.; Kamaruddeen, A. M.; Nawi, M. N. M.; Adeleke, A. Q.; Salimon, Maruf Gbadebo; Ajibike, W. A. (Elsevier, 2018)
Construction management scholars, institutional investors, and construction practitioners are strongly emphasizing firms’ needs to respond adequately to the harmful effects of construction on human societies and the environment. This study contributes to the ongoing discussion on the environmental dimension of the triple bottom line of sustainability within the construction industry by considering regulatory framework and a set of organizational capabilities (organizational culture, flexible design, quality orientation, product diversity, and customer loyalty) that have been highlighted to aid firms’ achievement of ecological sustainability. Using survey data of Malaysian large construction firms, structural equation modelling was used to confirm the mediating role of organizational capabilities in the regulatory framework and ecological sustainability relationship. The findings of this study established how proactive firm core competencies can strengthen construction businesses in developing nations to discover new avenues of performing environmentally sound construction businesses. It also demonstrated how a favourable regulation targeted at the unique configuration of large construction firms in Malaysian context could contribute to their environmental sustainability performance. The limitations and future research directions are also discussed.